Field Responsive Fluids as Smart Materials - Hajalilou, Abdollah; Amri Mazlan, Saiful; Lavvafi, Hossein; Shameli, Kamyar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This book is about field responsive fluids as smart materials, which includes magneto-rheological (MR) fluids, electro-rheological (ER) fluids and ferrofluids. It reviews the previous works and considers all the aspects that can help researchers and industries to choose proper materials as MR fluid constituents. Topics in magnetism and types of magnetic materials are presented. This includes the effect of magnetizable particles behaviors such as size, shape and density. The type of materials on the rheological properties is also compared for MR, ER and ferro-fluids. The second part of the book discusses advanced topics for MR, ER and ferro-fluids comparing some of the properties between the field responsive fluids. This book appeals to engineers, researchers and practitioners in the area of materials and mechanical engineering with interest in the field responsive fluids. .
Introduction -- Magnetism -- Magnetorheological (MR) Fluids -- Models between Shear Rate and Stress in MR fluids -- Magnetic particles sedimentation in MR fluids -- MR Fluid Applications -- Temperature Dependence of MR Fluids and their Components -- Electrorheological(ER)fluids -- Ferrofluids -- Properties of Field Responsive Fluids -- Conclusion.
Keywords: Optical materials; Fluid mechanics; Magnetism; Optical Materials; Engineering Fluid Dynamics; Magnetism